2005
DOI: 10.1359/jbmr.041009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear-Induced ATP Secretion Mediates Prostaglandin Release in MC3T3-E1 Osteoblasts

Abstract: ATP is rapidly released from osteoblasts in response to mechanical load. We examined the mechanisms involved in this release and established that shear-induced ATP release was mediated through vesicular fusion and was dependent on Ca 2+ entry into the cell through L-type voltage-sensitive Ca 2+ channels. Degradation of secreted ATP by apyrase prevented shear-induced PGE 2 release.Introduction: Fluid shear induces a rapid rise in intracellular calcium ([Ca 2+ ] i ) in osteoblasts that mediates many of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
214
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(236 citation statements)
references
References 51 publications
12
214
1
9
Order By: Relevance
“…3). We have shown that FSS produces a 10-fold increase in ATP release in MC3T3-E1 osteoblasts within 1 min of the onset of FSS (36). When primary osteoblasts from WT mice were subjected to steady laminar fluid flow at 12 dynes/cm 2 FSS, release of ATP was also observed within 1 min.…”
Section: P2x 7 R Null Micementioning
confidence: 75%
See 1 more Smart Citation
“…3). We have shown that FSS produces a 10-fold increase in ATP release in MC3T3-E1 osteoblasts within 1 min of the onset of FSS (36). When primary osteoblasts from WT mice were subjected to steady laminar fluid flow at 12 dynes/cm 2 FSS, release of ATP was also observed within 1 min.…”
Section: P2x 7 R Null Micementioning
confidence: 75%
“…ATP is an early mediator of mechanotransduction in osteoblasts that is released from cells within 1 min after applying mechanical loading (36). ATP initiates intracellular calcium release in osteoblasts through P2Y receptor pathways, which has been the main focus of several previous studies (15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, work on fluid flow has disclosed a prominent role of gap junction hemichannels in bone cells. Cx43 hemichannels are active in osteocytic cells, where they mediate fluid flow-induced PGE 2 [10] and ATP [59] release, although dependence of fluid flow stimulated release of ATP from osteoblastic cells has not been universally linked to Cx43 hemichannels [60]. One of the major challenges in this area is represented by the inherent difficulties in rigorously distinguishing hemichannel-mediated diffusion from exocytosis or other related events.…”
Section: Mechanisms Of Connexin Action In Bonementioning
confidence: 99%
“…The nucleotide concentration of the extracellular fluid aspirated from the hypertrophic zone of rat calcifying epiphyseal cartilage was reported to reach 1-2 mM (34). Nucleotides (ATP/UTP) are also released both by non-stimulated (35,36) or stimulated osteoblasts (37,38) in response to mechanical stimulus. The measured amount of secreted ATP in solution by murine osteoblast-like cell in response to shear was in the order of 100 nM, however this does not accurately show the local ATP concentration at the cell surface immediately on its release (38).…”
mentioning
confidence: 99%
“…Nucleotides (ATP/UTP) are also released both by non-stimulated (35,36) or stimulated osteoblasts (37,38) in response to mechanical stimulus. The measured amount of secreted ATP in solution by murine osteoblast-like cell in response to shear was in the order of 100 nM, however this does not accurately show the local ATP concentration at the cell surface immediately on its release (38). In addition, the osteoblasts have been shown to express an membrane-bound ecto-nucleoside diphosphokinase (ecto-NDPK), which allows the ADPuATP conversion in extracellular calcification medium (35).…”
mentioning
confidence: 99%